The Timing of Purchases and Aggregate Fluctuations - Leahy, John V.; Zeira, Joseph (Review of Economic Studies, 2005)
We study the cyclical effects of the timing of durable goods purchases in a general equilibrium model in which both durable and non-durable goods are consumed and the durable good is lumpy, At the microeconomic level, the timing of durable goods purchases supplies some insulation for nondurable consumption over the cycle. At the macroeconomic level, the timing decisions tend to amplify and propagate wealth and income shocks. Our model also allows for endogenous price determination. When the price of the durable changes due to inflexibility of workers between sectors, the effect of adverse shocks is even stronger and longer.